Changing Ecosystem - Social System Links and Future of Drylands in India - Jodha, N S (Annals of Arid Zone, 2016)
This paper synthesized the inferences and understanding of various studies and observations focussed on nature-society interaction patterns, and their driving circumstances and consequences in the arid and semi-arid areas of India. Faced with high risk-low productivity situations in dry lands, the communities have histrocially evolved various resource use and produciton practices. They reflect a two-way adaptation process, i.e. adapting human needs to limitation and potential of natural resource base and adapting or amending nature (as far as possible) to increasing human needs. This two way adaptation process has been weakned due to the side effects or modem changes rooted in state policies, market forces and various socio-economic changes. The paper suggests the needs and approaches to identify and integrate the elements of traditional adaptations into future strategies for development of drylands. Key issues are covered in the paper and summarized under table